2014
DOI: 10.1093/bja/aeu051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supervised aerobic exercise rehabilitation on physical fitness and quality-of-life in survivors of critical illness: an exploratory minimized controlled trial (PIX study)

Abstract: BackgroundEvidence is limited for the effectiveness of interventions for survivors of critical illness after hospital discharge. We explored the effect of an 8-week hospital-based exercise-training programme on physical fitness and quality-of-life.MethodsIn a parallel-group minimized controlled trial, patients were recruited before hospital discharge or in the intensive care follow-up clinic and enrolled 8–16 weeks after discharge. Each week, the intervention comprised two sessions of physiotherapist-led cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 30 publications
5
96
0
3
Order By: Relevance
“…Our study has several limitations; only a small proportion of patients screened and survived to hospital discharge were recruited (7.8%), which has implications for generalisability of the findings, although this is similar to the recruitment rate in the other rehabilitation studies following hospital discharge in this population 5 8. Identification of which patients will benefit most from an exercise intervention based on baseline status has not yet been explored in the critical care population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our study has several limitations; only a small proportion of patients screened and survived to hospital discharge were recruited (7.8%), which has implications for generalisability of the findings, although this is similar to the recruitment rate in the other rehabilitation studies following hospital discharge in this population 5 8. Identification of which patients will benefit most from an exercise intervention based on baseline status has not yet been explored in the critical care population.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies with supervised programmes have demonstrated some benefit,3 5 7 whereas a home-based study that did not incorporate a high level of supervision was unable to demonstrate improved outcomes 8. Supervision or support may be an important component of rehabilitation as it has been suggested that exercise can be difficult for people to perform without feedback about their performance or help to modify and progress the exercises 40…”
Section: Discussionmentioning
confidence: 99%
“…The ideal scenario may be a blurring of the lines between prehabilitation and enhanced recovery, such that one programme leads into the next, punctuated by surgery, with minimal interruption. This idea is particularly appealing in the case of exercise, where evidence suggests that early postoperative exercise rehabilitation enhances the recovery of functional status [57,58]. There is some evidence that the pre-operative period may represent a more appropriate time than the postoperative period to implement an intervention [59]; however, further research is needed to determine if a combination of prehabilitation plus early rehabilitation is superior to prehabilitation alone.…”
Section: Multi-modal Prehabilitation and Rehabilitationmentioning
confidence: 99%
“…Four studies reported rates of withdrawal, which ranged from 0% to 26.5% in control groups and from 8.2% to 27.6% in intervention groups . The quality of evidence for the effect of the intervention on withdrawal was low.…”
Section: Resultsmentioning
confidence: 96%